FARMERS' BUSINESS IN OVERCOMING THE PROBLEM OF FAILED HARVEST OF RICE (Oryza sativa) IN PADANG LAWAS UTARA DISTRICT: USAHA PETANI DALAM MENGATASI PERMASALAHAN GAGAL PANEN PADI SAWAH (Oryza sativa) DI KABUPATEN PADANG LAWAS UTARA - Suci Ayu Harahap, Putri (UPMI Proceeding Series, 2023)
Maintenance on plant paddy ricefield very needed For get high production . _ Study This aim For know factors For enhancement production plant rice . Data used in study This is secondary data from a number of different sources . _ Wrong One method used _ in study This with method provision seed quality in activity food estate. processing regular irrigation _ with make distribution of irrigation water . And control pest And disease on plant rice . In his research There are 3 ( three ) types method provision of irrigation water For paddy , that is continuous waterlogging _ continuous , continuous flow of water continuously And intermittent water flow . Besides That Wrong One method control pest badger fierce on plant paddy is use pesticide made from smoke liquid shell coconut . Where application pesticide organic with smoke liquid shell coconut with concentration 8 % had total mortality badger fierce biggest that is equivalent with 100% ( Table 1). Mark mortality increase along with enhancement mark concentration on treatment . Based on test Anova that has held is known that mortality data the significant And gift pesticide organic origin _ from smoke liquid shell coconut can influence death badger sangit. Stage then the data will be reviewed use 5% DMRT test . The result every treatment different real One The same other .